Technological innovations and lessons learned in Indonesia's Rice Traceability Program - Walton, Jenny (International Food Policy Research Institute, 2024)
The traceability of food supply chains is crucial for ensuring food safety, supporting ethical practices, and protecting product value. In Indonesia, a nation highly reliant on rice as its staple food, advancements in digital traceability systems have been instrumental in addressing malnutrition and improving food security. This brief highlights key technological innovations and lessons learned from the efforts to enhance traceability within Indonesia’s zinc-biofortified rice program.